The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/iwj.14526
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of electroacupuncture in among early diabetic patients with lower limb arteriosclerotic wounds

Peng Sang,
Jiahui Zhao,
Hui Yang

Abstract: Diabetic foot ulcers are the prevalent complication of diabetes mellitus, frequently culminating in arteriosclerosis of the lower extremities and consequent development of chronic wounds. The effectiveness of electroacupuncture (EA) as therapeutic intervention for promoting wound healing in this particular group of patients has been comprehensively assessed in this study. A randomized controlled trial involving 380 early diabetic patients with arteriosclerotic lesions of the lower limbs was conducted. Standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Although these differences are only a trend, as they did not reach statistical significance for every microcirculatory parameter measured, the reason for these differences is not clear. Our findings in patients with DFS are consistent with those recently published by Sang et al, who showed that diabetic patients with arteriosclerotic wounds of the lower extremity had a significant reduction in lesion size after 8 weeks of treatment with electroacupuncture (56). An exact explanation of the precise acupuncture mechanisms of our observed effects can only be hypothesized.…”
Section: Discussionsupporting
confidence: 93%
“…Although these differences are only a trend, as they did not reach statistical significance for every microcirculatory parameter measured, the reason for these differences is not clear. Our findings in patients with DFS are consistent with those recently published by Sang et al, who showed that diabetic patients with arteriosclerotic wounds of the lower extremity had a significant reduction in lesion size after 8 weeks of treatment with electroacupuncture (56). An exact explanation of the precise acupuncture mechanisms of our observed effects can only be hypothesized.…”
Section: Discussionsupporting
confidence: 93%